Respuesta :

Answer:

D

Step-by-step explanation:

a p e x

The explicit rule of the sequence is (d) [tex]a_n = 8-6 (n -1)[/tex]

How to determine the explicit formula?

The sequence is given as:

a1 = 8

[tex]a_n = a_{n-1} - 6[/tex]

Set n = 2

[tex]a_2 = a_{1} - 6[/tex]

This gives

a2 = 8 - 6

a2 = 2

Calculate the common difference (d)

d = a2 - a1

This gives

d = 2 - 8

Evaluate

a = -6

The explicit formula is then calculated as:

[tex]a_n = a_1 + (n -1)d[/tex]

This gives

[tex]a_n = 8-6 (n -1)[/tex]

Expand

[tex]a_n = 8-6n +6[/tex]

Evaluate the like terms

[tex]a_n = 14-6n[/tex]

Hence, the explicit rule of the sequence is (d) [tex]a_n = 8-6 (n -1)[/tex]

Read more about sequence at

https://brainly.com/question/6561461

#SPJ6